Artificial Intelligence and Trends in Use of Information Technology Governance: A Bibliometric Analysis (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This study aims to provide an overview of the development of information technology governance (ITG) and Artificial Intelligence (AI) research published in the Scopus database to track the development of scientific activities that could pave the way for future studies by highlighting gaps in this field. Four hundred fifty-five studies were identified in this field, from 2007 to 2025. Our analysis focused on 233 research papers related to ITG and AI from 2015 to 2024. Based on bibliometric analysis using VOS viewer, this paper highlights the prevailing trend of current research in the field of AI and ITG by providing a detailed bibliometric analysis of the trend and development of research for the last ten years due to the increasing reliance on AI by banks, which was also accompanied by an increase in the number of banks sponsoring AI, including investigating countries, journals and keywords of research. The results indicate that researchers using AI and ITG have converged in using technology between developing and developed countries alike. We also found through the VOSviewer analysis that the decision-making process is the main reason for the ITG trend towards using AI. The countries with the most publications and the most common keywords were selected. This paper provides evidence of the lack of many banks in different countries resorting to AI. Finally, the data analysis identifies many potential research issues that need to be investigated regarding the relationship between ITG and AI, which serve as an area for future research. Again, this study also provides a framework for banks to pay attention to areas related to AI.